Analisis Bkm Sebagai Lembaga Yang Bergerak Dibidang Pelayanan Lansia Di Masjid Al-Ikhlas - Ramadhan Lubis; Aliya Anggraini; Apra Mutiara Ramadani; Faiz Al Rafif; Indah Karina Manik; Laila Tussifa Harahap; Riski Nabila (CV. ITTC INDONESIA, 2025)
This study aims to discuss and describe how institutions provide services to the elderly. The institutions in question are mosques. The focus of the study includes forms of collaboration, program development, and the objectives of these institutions to meet the needs of the elderly. The research was conducted by gathering information and observing elderly service institutions. The analysis shows that these institutions have core programs, such as assistance with daily activities and social support, to improve the quality of life of the elderly. However, several challenges remain, such as limited facilities and financial constraints. Elderly service institutions make an important contribution to meeting the needs of the elderly, but they need to improve the quality of service and resource support. This article concludes that optimizing elderly services in mosques needs to be strengthened through collaboration between mosque administrators, the community, and relevant agencies to improve the overall quality of life of the elderly